Big Data in the travel marketplace. Issue 5 (October 2016) - Vinod, Ben
Abstract We are beginning to see that Big Data will have a profound impact on gaining consumer insights, improving process efficiencies and enhancing the consumer experience. In the travel industry, travel suppliers, Online Travel Agencies and Global Distribution Systems have access to vast amounts of data from across the travel value chain – marketing and lead generation, interactive selling, fulfillment and customer care. Big Data can offer unique insights into consumer preferences and behavior patterns to improve conversion rates and revenues. This article focuses on the role of Big Data, the skills required in an organization to leverage Big Data in travel followed with examples of Big Data applications related to travel as it applies to suppliers, online and traditional travel agencies.